A hedonic analysis of nutrition labels across product types and countries. (25th October 2017) - Edenbrandt, Anna Kristina; Smed, Sinne; Jansen, Léon
Abstract: Consumers' use and valuation of nutrition labels is mainly analysed based on stated attitudes or stated use of such labels. This study is based on household scanner data from the Netherlands and Denmark, and includes a range of different products. Hedonic price models are estimated and the results show positive values attached to the label across countries and most product categories, suggesting that consumers do value the guidance that the nutrition labels provide. Policy implications from these results indicate that credible nutrition labels are relevant tools in the effort to combat diet-related diseases by guiding consumers towards healthier diets.